PENGARUH KOMPETENSI DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN PROBOLINGGO - Kusumawardana, Dhika; Halim, Abdul; Rosidi, Rosidi (Al-Idarah, 2023)
Competence is the knowledge, skills and abilities possessed by individuals that havebeen attached to theird behavior in various circumstances and work assignments.This research is a quantitative research with an approach to the research method ofexplanation. The sample used is 51 employee respondents from work unitrepresentatives. The analysis used is path analysis. By using SPSS 25 calculation.The results showed that competence had significant effect on job satisfaction, jobplacement has a significant effect on job satisfaction, competence has significanteffect on performance; iv) job placement has a significant effect on performance, jobsatisfaction has significant effect on performance, the direct effect of competence onperformance is greater than the indirect effect on competence through jobsatisfaction, the direct effect of job placement on performance is greater than theindirect effect on job placement through job satisfaction.Keywords : Competence, Job Placement, Job Satisfaction, Performance